The anatomy of human misery and its therapy : a study of miracles and healing in the life of our Lord and in the early church, until the Council of Nicaea - Hawkridge, John Bernard (Rhodes University, Faculty of Divinity, Department of Divinity, 1959)
This thesis seeks to show that miracles and healing are inseparable from the Messianic task of Jesus Christ; and that in so far as He commissioned His Church to continue that Messianic task, it is reasonable to expect that miracles and healing would continue. The early history of the Church is examined for evidence confirming this expectation, and a question is asked of the contemporary Church.
Keywords: Jesus Christ -- Miracles; Spiritual healing -- Psychological aspects; Healing in the Bible; Church history